1993
DOI: 10.1111/j.1528-1157.1993.tb02598.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Night Sleep Duration and Seizure Frequency in Temporal Lobe Epilepsy

Abstract: Correlations between occurrence of complex partial seizures and altered sleep duration were analyzed in a small but strongly homogeneous population of temporal lobe epilepsy patients. Sleep deprivation and oversleep were determined individually; 682 epileptic seizures occurring on 4,995 days were related to occasional alterations of night sleep duration. The seizure-inducing effect of an actual relative sleep deprivation was 67-100% in four cases and 49-64% in four cases. Oversleep had no consistent seizure-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 19 publications
0
51
0
1
Order By: Relevance
“…For each 10 s segment, eyes were opened and closed for 5 s each. The trains were performed at frequencies of 1, 2, 4, 6,8,10,12,13,14,15,16,17,18,20,25,30,50 and 60 Hz. At least 30 min of artifact-free signals were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each 10 s segment, eyes were opened and closed for 5 s each. The trains were performed at frequencies of 1, 2, 4, 6,8,10,12,13,14,15,16,17,18,20,25,30,50 and 60 Hz. At least 30 min of artifact-free signals were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, increased lateralizing and localizing values were reported for interictal epileptiform discharges occurring in NREM (non-rapid eye movement) sleep stages [7,9,12]. Precipitation of epileptic activities and seizures upon sleep and during sleep deprivation were reported in patients with confirmed epilepsy [13,14]. However, the utility of sleep EEG recordings in new-onset epilepsy with a normal EEG during wakefulness is unclear and should be proven by well-designed prospective studies.…”
Section: Introductionmentioning
confidence: 95%
“…Particularly, it could be argued that fever should be considered a facilitating rather than a triggering factor as it generically lowers the seizure threshold rather than inducing seizure occurrence directly. The same may be true for sleep deprivation [16][17][18], alcohol withdrawal, exposure to drugs [19], toxins such as heavy metal or carbon monoxide poisoning which have also been associated with seizure occurrence [20,21]. Further reference to triggers can be found in studies assessing the link between hormonal changes during the menstrual cycle [22] or metabolic disturbances such as hypoglycaemia, renal encephalopathy or hepatic failure [9,23] and seizure occurrence.…”
Section: Triggers In Seizuresmentioning
confidence: 97%
“…Rajna and Veres (1993) examined seizures diaries, sleep duration and PS in 14 patients with TLE for a period of 4995 days. It was demonstrated that even decrements of 1.5 h from patients' mean sleep time resulted in an increase of seizures.…”
Section: Sleep Reductionmentioning
confidence: 99%